ҲАРБИЙ АУДИТОРИЯГА ИНГЛИЗ ТИЛИДА SCHWA /Ə/ ТОВУШИНИ ЗАМОНАВИЙ УСУЛЛАР ОРҚАЛИ ЎҚИТИШНИНГ ЎЗИГА ХОСЛИГИ - Раджабов, Н.Н. (SCIENCE and SOCIETY, 2022)
The article is devoted to the analysis of the peculiarities of teaching English Schwa /ə/ to the military audience by modern methods. It explores several modern methods of teaching the Schwa /ə/ sound and reveals their aspects that need to be considered when using them in the military audience. The article also develops a special way of teaching English Schwa /ə/ to the military audience. The suggested method is called “Schwa Spelling and Pronunciation” and its application and advantages are explained in detail.
Keywords: sound; letter; Schwa sound; neutral / a / vowel; accent; accented syllable; unstressed syllable